First observation of Λ c (2595)+ → Λ c + π 0 π 0 $$ Λ_c^{+}{π}^0π^0 $$ and Λ c (2625)+ → Λ c + π 0 π 0 $$ Λ_c^{+}{π}^0π^0 $$ - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Journal of High Energy Physics)
Abstract By analysing e + e − annihilation data corresponding to an integrated luminosity of 368.48 pb −1 collected at the centre-of-mass energies of s $$ \sqrt{s} $$ = 4.918 and 4.951 GeV with the BESIII detector, we report the first observation of Λ c (2595)+ and Λ c (2625)+ → Λ c + π 0 π 0 $$ Λ_c^{+}{π}^0π^0 $$ with statistical significances of 7.9σ and 11.8σ, respectively. The branching fractions of Λ c (2595)+ and Λ c (2625)+ → Λ c + π 0 π 0 $$ Λ_c^{+}{π}^0π^0 $$ are measured to be (59.5 ± 11.1stat. ± 7.9syst. )% and (41.0 ± 5.2stat. ± 3.3syst. )%, respectively. The absolute branching fraction of Λ c (2595)+ is consistent with the expectation of the mechanism referred to as the threshold effect, proposed for the strong decays of Λ c (2595)+ within uncertainty.